An empirical vegetation correction for soil water content quantification using cosmic ray probes. Issue 4 (8th April 2015) - Baatz, R.; Bogena, H. R.; Hendricks Franssen, H.‐J.; Huisman, J. A.; Montzka, C.; Vereecken, H.
Abstract: Cosmic ray probes are an emerging technology to continuously monitor soil water content at a scale significant to land surface processes. However, the application of this method is hampered by its susceptibility to the presence of aboveground biomass. Here we present a simple empirical framework to account for moderation of fast neutrons by aboveground biomass in the calibration. The method extends the N 0 ‐calibration function and was developed using an extensive data set from a network of 10 cosmic ray probes located in the Rur catchment, Germany. The results suggest a 0.9% reduction in fast neutron intensity per 1 kg of dry aboveground biomass per m 2 or per 2 kg of biomass water equivalent per m 2 . We successfully tested the novel vegetation correction using temporary cosmic ray probe measurements along a strong gradient in biomass due to deforestation, and using the COSMIC, and the hmf method as independent soil water content retrieval algorithms. The extended N 0 ‐calibration function was able to explain 95% of the overall variability in fast neutron intensity. Key Points: Soil water content was determined accurately with cosmic ray probes An empirical linear correction for variable aboveground biomass was developed The COSMIC operator, N 0 and the hmf method were used for evaluation